Are shocks to energy consumption permanent or temporary? The case of 17 middle east countries - Ozcan, Burcu (Sage Publications Inc, 2013)
This article applies the univariate and panel LM (Lagrange Multiplier) unit root tests developed by Lee and Strazicich (2003; 2004) and Im et al. (2005), respectively to annual total primary energy consumption per capita data for 17 Middle East countries over the period 1980-2009. The results from univariate tests with one and two structural breaks indicate that stationarity does hold for most of the Middle East countries, especially in the case of two structural breaks. Furthermore, panel LM unit root tests have overwhelming evidence favorable to stationarity in both cases. These results indicate that shocks to energy consumption have only temporary effects and thus, energy demand management or conservation policies will not reach their targets in the long-run.
Keywords: Energy consumption; Energy policy; Structural breaks; Panel unit root tests